GlacioTools: Streamlining Glacier Feature Monitoring and Reporting in QGIS - S. Fajardo Turner; F. Gaspari; F. Migliaccio (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Mountain glaciers are highly sensitive to climate change, having lost nearly half their surface area and two-thirds of their volume in the European Alps since 1850. Recent advances in unmanned aerial vehicles (UAVs) and aerial imagery, combined with traditional in-situ Ground Control Points (GCPs) measurements, have enabled repeated data collection for glacier monitoring. However, analyzing and visualizing glacier changes remains a time-consuming process in Geographic Information System (GIS) environments.  QGIS, an open-source GIS, supports custom plugins that automate routine tasks, improving accessibility and collaboration in climate research. Existing plugins facilitate environmental monitoring, hydrology, and remote sensing applications, streamlining spatial analysis without requiring programming expertise. Despite these tools, an integrated, user-friendly solution for glacier monitoring is still lacking. In this paper the GlacioTools QGIS plugin is presented. It is designed to simplify geospatial data processing for glacier studies. It automates in-situ survey reporting, generates surface displacement and velocity maps, and organizes GCP documentation within a single workflow. By enhancing efficiency and accessibility, GlacioTools supports researchers in documenting and analyzing glacier evolution more effectively.